2019
DOI: 10.17576/jsm-2019-4805-14
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Irrational’ Taboos and ‘Irrelevant’ Traditions Related to Postpartum Women’s Health and Well-Being

Abstract: Taboos and traditions refer to myths and non-scientific practices held by people across the world. A variety of taboos are practiced worldwide (including those relating to food, religious, and sexual beliefs), including in Malaysia. Most of the taboos that concern the postpartum period are related to postpartum physiological, emotional, and family dynamic changes. The aim of this systematic review is to explore the traditions and taboos practised among postpartum mothers in Malaysia, and to consider the purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…While the information is accurate, HCPs need to better understand patients' cultural and social expectations to ensure effective communication. In this instance, most ethnicities in Malaysia have cultural beliefs on food prohibited during cancer [ 33 , 34 ] or other life events such as pregnancy or postpartum [ 35 37 ]. With this understanding, HCPs can spend some time debunking the "myths" that patients might have and tailor their advice according to cultural expectations while providing health information.…”
Section: Discussionmentioning
confidence: 99%
“…While the information is accurate, HCPs need to better understand patients' cultural and social expectations to ensure effective communication. In this instance, most ethnicities in Malaysia have cultural beliefs on food prohibited during cancer [ 33 , 34 ] or other life events such as pregnancy or postpartum [ 35 37 ]. With this understanding, HCPs can spend some time debunking the "myths" that patients might have and tailor their advice according to cultural expectations while providing health information.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in Malaysia indicated that low energy intake among lactating women was affected by food restriction due to a belief that lactating mothers were in a "cold state" after delivery. Restriction of consuming certain types of foods was believed to balance the hot and cold states of the body (29,88).…”
Section: Macronutrient Intakementioning
confidence: 99%
“…The existence of food taboos among pregnant women in some cultures to certain protein source foods such as seafoods may hinder the consumption of these foods. It was believed that these foods contained high cholesterol and caused complications during delivery (29,88). Furthermore, a high protein intake in pregnant and lactating women in Malaysia followed the same intake pattern of Malaysian adults.…”
Section: Macronutrient Intakementioning
confidence: 99%